Peningkatan Efektivitas Layanan Restoran melalui Aplikasi GUI yang Interaktif - Ridwan Potabuga; Fajar Husain Asy’ari; Varly Carnavale Wullur; Kezia Queensi Rori (Lembaga Pengembangan Kinerja Dosen, 2023)
A simple restaurant application is a program that can be used to manage food and drink menu orders at a restaurant. This application uses a graphical user interface (GUI) that is easy to use and interactive. The aim of developing this application is to increase the effectiveness of restaurant operations, such as speeding up the ordering process, reducing errors, and increasing customer satisfaction. This application also has advantages such as being easy to learn, flexible, and can run on various operating systems. This application is expected to be a solution for restaurants who want to improve their performance and service. Development of a Simple Restaurant Application with a Graphical User Interface (GUI) to Increase Operational Effectiveness. In an ever-evolving digital era, the restaurant industry faces increasing pressure to improve operational efficiency and provide better experiences to customers. This research proposes the development of a simple restaurant application equipped with a graphical user interface (GUI) as an innovative solution to improve operational effectiveness. The research method used is development research, involving literature studies to understand the latest developments in restaurant applications and graphical user interface technology. Analysis of user needs is carried out through interviews with restaurant managers and customers to determine the features and functions needed.